Politics in Congo : Decolonization and Independence - Young, Crawford, 1931- (Book collections on Project MUSE., 1965)
The process of decolonization, the development of the nationalist movement, and the salient aspects of the emerging post-independence policy in the Congo since 1954 are studied. Special emphasis is given to the forces set loose by the Leopoldville explosion.Originally published in 1965.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.